2023
DOI: 10.7189/jogh.13.06030
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection and mortality among non-pregnant indigenous adults in Mexico 2020-2022: Impact of marginalisation

Bert B Little,
Shaminul Shakib,
Maria E Pena Reyes
et al.

Abstract: Background Indigenous individuals have higher rates of mortality and poverty in Mexico and more than half are marginalised, and COVID-19 pandemic aggravated the existing burden of health disparities. We aimed to analyse the effects of being indigenous and marginalised on coronavirus (COVID-19) infection fatality in Mexico. Methods We identified 3 424 690 non-pregnant, COVID-19 positive adults ≥19 years in the Mexico national COVID-19 database with known date of symptom.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…These communities tend to be older and have higher comorbidity rates, leading to worse COVID-19 outcomes [ 17 , 18 ]. Factors like marginalization and comorbidities further elevate the risk of COVID-19 fatality among Indigenous individuals [ 19 ]. Additional studies have revealed that Indigenous people receiving outpatient management experienced a higher fatality rate than non-Indigenous outpatients [ 14 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These communities tend to be older and have higher comorbidity rates, leading to worse COVID-19 outcomes [ 17 , 18 ]. Factors like marginalization and comorbidities further elevate the risk of COVID-19 fatality among Indigenous individuals [ 19 ]. Additional studies have revealed that Indigenous people receiving outpatient management experienced a higher fatality rate than non-Indigenous outpatients [ 14 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%